2022
DOI: 10.2147/jpr.s337465
|View full text |Cite
|
Sign up to set email alerts
|

Migraine Attacks and Relevant Trigger Factors in Undergraduate Nursing Students in Hong Kong: A Cross-Sectional Study

Abstract: Objective This study aimed to examine the prevalence and features of migraine and explore the possible migraine triggers in a sample of university nursing students in Hong Kong. Methods A cross-sectional study using self-administered questionnaires was conducted in the Hong Kong Polytechnic University in 2016. The questionnaire included ID Migraine™ for migraine screening and items measuring the frequency, duration, severity, associated symptoms, and trigger factors of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 46 publications
1
10
0
Order By: Relevance
“…Reports indicate that the prevalence of lower back pain among ICU nurses worldwide over the last year ranged from 34.5% 22 to 100%, 21,23 with nursing positions in critical care units requiring considerably higher levels of physical exertion, such as long periods of standing for hours, heavy workloads, shift work, patients with complex health problems, and frequent emergency conditions and death; thus, the risk level of ICU nurses is much higher than that of nurses who work in other units. 8 Moreover, limited data are available on the pain levels experienced by ICU doctors and workers among ICU workers; these values are comparable to those found among the general East Asian population 10 and undergraduate nursing students in Hong Kong; 24 Thus, this issue warrants further attention. We found that bending or twisting of the neck was associated with pain and that the neck was the main body location where ICU doctors reported feeling pain.…”
Section: Discussionmentioning
confidence: 94%
“…Reports indicate that the prevalence of lower back pain among ICU nurses worldwide over the last year ranged from 34.5% 22 to 100%, 21,23 with nursing positions in critical care units requiring considerably higher levels of physical exertion, such as long periods of standing for hours, heavy workloads, shift work, patients with complex health problems, and frequent emergency conditions and death; thus, the risk level of ICU nurses is much higher than that of nurses who work in other units. 8 Moreover, limited data are available on the pain levels experienced by ICU doctors and workers among ICU workers; these values are comparable to those found among the general East Asian population 10 and undergraduate nursing students in Hong Kong; 24 Thus, this issue warrants further attention. We found that bending or twisting of the neck was associated with pain and that the neck was the main body location where ICU doctors reported feeling pain.…”
Section: Discussionmentioning
confidence: 94%
“…Xie et al recorded the duration of headache as the average number of hours for a typical headache attack and found that the average duration of a migraine attack was 3 (interquartile range: 1–4) hours. 3 In the study, the authors did not indicate how long headache lasted amongst the medical students (2022).…”
mentioning
confidence: 89%
“…These have allowed studies to achieve comparable statistics on the prevalence, incidence, and course of diseases. 8 Particularly, the introduction of "explicit diagnostic criteria for headache syndromes" in 1988 by the International Headache Society (IHS) was a cornerstone in migraine assessment. 8 Accordingly, the three-item Identification of Migraine (ID Migraine), a brief self-administered screening test, was developed and validated as a practical tool to diagnose possible migraine cases.…”
Section: Introductionmentioning
confidence: 99%
“…8 Particularly, the introduction of "explicit diagnostic criteria for headache syndromes" in 1988 by the International Headache Society (IHS) was a cornerstone in migraine assessment. 8 Accordingly, the three-item Identification of Migraine (ID Migraine), a brief self-administered screening test, was developed and validated as a practical tool to diagnose possible migraine cases. 9 Previous studies reported a higher prevalence of migraine among women 10 and adults between 20 and 65 years of age.…”
Section: Introductionmentioning
confidence: 99%